Modification of pervious concrete using steel slag as an aggregate replacement : application at Pekan, Pahang, Malaysia - Yafouz, Ayman Mohammed Shaher (2019)
Floods are the most significant natural disasters which affect 4.9 million people and inflict damage worth of several million every year in Malaysia. About 29,720 Km2 or 9% of the land area of the country is prone to flooding. Pekan town is located on the banks of the Pahang River, regularly suffers both economic damages and physical destructions caused by the floods. This study is a try to determine the suitable pervious concrete that can be used effectively at Jalan Kuantan – Pekan which experienced high direct runoff. The goal of this research is to prevent or at least minimizing hastily the direct runoff on the pavement and preserve their natural characteristics. Indeed, this study is progressed in two stages; 1st stage is obtaining the best mix design out of the preliminary result which consist of 48 samples of cubic concrete samples with dimension of 100mm based on 7 days compressive strength test. Then, different proportion of aggregate and water/cement ratio will be tested in order to select the highest compressive strength to be used in the 2nd stage. In the 2nd stage, there are 12 samples of cylindrical concrete with dimension of 200mm in height *100mm in diameter. Steel slag is used in the 2nd stage besides the granite aggregate. In fact, the steel slag is involved in terms of three different of percentage as 70% Granite and 30% Steel Slag, 50% Steel Slag and 50% Granite and 30% Granite and 70% Steel Slag. Also, Infiltration rate will be tested throughout permeability test. Oppositely, the main aspect that generating the obstacle on the pavement which is the rainfall intensity will be identified. Thus, Intensity Distribution Frequency IDF curve of rainfall of Rumah Pam Pahang Tua Station at site 3533102 will be developed by using MSMA 2nd edition to be compared with infiltration rate results of pervious concrete and to determine the suitability of the pervious concrete to be used.